2017
DOI: 10.1080/13510002.2017.1311464
|View full text |Cite
|
Sign up to set email alerts
|

Plasma low-molecular-weight thiol/disulphide homeostasis as an early indicator of global and focal cerebral ischaemia

Abstract: These results suggest that plasma low-molecular-weight thiols are actively involved in oxidation reactions at early stages of cerebral ischaemia; therefore, their reduced forms or redox state may serve as a sensitive indicator of acute cerebrovascular insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
1
8
1
3
Order By: Relevance
“…The resulting disulfide bond structures are again reduced to thiol groups so that the thiol/disulfide balance is maintained [ 7 ]. Diseases including diabetes mellitus [ 8 ], obesity [ 9 ], cardiovascular disease [ 10 ], hypertension [ 11 ], malignancy [ 12 ], rheumatic disease, chronic renal failure [ 13 ], Alzheimer's disease [ 14 ], chronic liver disease [ 15 ], cerebral ischemia [ 16 ], nasal polyposis [ 17 ], preeclampsia [ 18 ], uterine myoma [ 19 ], cataracts [ 20 ], chronic radiation exposure [ 21 ], and acute tonsillopharyngitis [ 22 ] have been assessed by the same method used in our study, and a close relationship with oxidative stress was detected. A strong association between familial hypercholesterolemia and premature atherosclerotic cardiovascular disease was established in a study conducted with 1,690 patients [ 1 ], and, in our study, we found that disulfide formation was elevated in patients with familial hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting disulfide bond structures are again reduced to thiol groups so that the thiol/disulfide balance is maintained [ 7 ]. Diseases including diabetes mellitus [ 8 ], obesity [ 9 ], cardiovascular disease [ 10 ], hypertension [ 11 ], malignancy [ 12 ], rheumatic disease, chronic renal failure [ 13 ], Alzheimer's disease [ 14 ], chronic liver disease [ 15 ], cerebral ischemia [ 16 ], nasal polyposis [ 17 ], preeclampsia [ 18 ], uterine myoma [ 19 ], cataracts [ 20 ], chronic radiation exposure [ 21 ], and acute tonsillopharyngitis [ 22 ] have been assessed by the same method used in our study, and a close relationship with oxidative stress was detected. A strong association between familial hypercholesterolemia and premature atherosclerotic cardiovascular disease was established in a study conducted with 1,690 patients [ 1 ], and, in our study, we found that disulfide formation was elevated in patients with familial hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…The close relationship between the plasma and cerebral LMWTs pools has been shown in experimental models of cerebral ischemia. In first, a decrease in RS of LMWTs in plasma was detected in a model of acute focal and global brain ischemia, that was accompanied by a decrease in rGSH content or an increase in oxidized GSH in brain tissue [ 17 , 18 ]. Secondly, the ability of GSH to alleviate of brain injury when it is injected into the blood was shown in the model of transient focal cerebral ischemia [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were mixed thoroughly, frozen, and stored at –80°C. The t-, r-forms, and the RS of Cys, Hcy, and GSH were determined by liquid chromatography as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Эксперименты проводили на наркотизированных хлоралгидратом (300 мг/кг, в/б) беспородных крысах-самцах (n = 20) массой 260-300 г. Мозговой кровоток регистрировали в теменном неокортексе лазерным допплеровским флоуметром ЛАКК-02 (Лазма, Россия) по описанной ранее методике [3]. Регистрацию системного АД в бедренной артерии осуществляли монитором MEC8 (Mindray, Chine).…”
Section: материал и методы исследованияunclassified